Razão áurea : uma proposta para o ensino de geometria - Lopes, Edvania Portilho (2022)
In this work, we present a bit of the history of the golden ratio, showing how it is present in nature, art, architecture, the human body, Fibinacci numbers, plane geometry and also spatial geometry. We present some works on the golden ratio in sacred geometry. We performed some calculations showing interesting results in plane geometry. Finally, we elaborated a didactic proposal involving geometric constructions and golden ratio, with the purpose of involving basic education students in the teaching of geometry.